Cambodia Sanitation Marketing - World Bank (Washington, DC, 2015)
This report synthesizes the technical assistance (TA) “Cambodia Sanitation Marketing” carried out by the World Bank’s Water and Sanitation Program (WSP) from July 2011 to February 2015 in support of developing the rural sanitation market in Cambodia. It documents the results and lessons learned and makes recommendations to government on how - with support of development partners – the effectiveness and scale of the sanitation market can be increased to achieve sustainable sanitation outcomes for rural Cambodians. This TA is part of a larger support program to assist the Government of Cambodia, notably the Ministry of Rural Development, to increase access and use of improved sanitation in rural areas of Cambodia. Technical Assistance P132212 is a complementary effort that focusses on strengthening the policy and enabling environment for rural sanitation service delivery at national and sub-national level. The following lessons were learned from the TA: (1) the local private sector has catered more than 50,000 latrines to rural households, (2) the provinces where the TA was taking place experienced an average 10 percentage point increase in overall sanitation access, more than three times the national average increase within the same time period, (3) the increase in sanitation access among the poor was eight percentage point indicating the challenges that the private sector has in reaching the poorer segment of the population, (4) the private sector’s revenue was estimated to amount to nearly USD 2.6 million from the sales of the underground latrine core, and (5) more than USD 600,000 was disbursed by two microfinance institutions (MFIs) to nearly 10,000 cash constrained households, enabling them to gain access to improved sanitation.